1997
DOI: 10.1007/bf01740813
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to diphtheria-tetanus-pertussis vaccine components in Argentine children

Abstract: The Argentine vaccination schedule against diphtheria, tetanus and pertussis (DTP) recommends three doses of DTP vaccine at 2, 4 and 6 months of age, two boosters at 18 months and 6 years, a booster dose of tetanus vaccine every 10 years and two doses during pregnancy. To evaluate the effect of this schedule, antibodies against pertussis toxin (PT) and filamentous hemagglutinin (FHA) and against tetanus and diphtheria toxoids were determined by ELISA in serum samples from children (1 month to 6 years) who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It was also observed that antibodies against PT increased as the number of DPaT doses increased (at 2, 4 and 6 months). Pasetti et al 28 reported that complete protection is not achieved after 3 doses. This occurs after the first booster has been applied.…”
mentioning
confidence: 99%
“…It was also observed that antibodies against PT increased as the number of DPaT doses increased (at 2, 4 and 6 months). Pasetti et al 28 reported that complete protection is not achieved after 3 doses. This occurs after the first booster has been applied.…”
mentioning
confidence: 99%
“…Long‐term studies have shown that most horses have titres of more than 0.01 IU/ml for 5–8 years after basic immunisation. This recommendation is a direct extrapolation from recommendations for protective titres in humans (Pasetti et al., 1997), which in turn were based on guinea pig studies (Sneath et al., 1937).…”
Section: Discussionmentioning
confidence: 99%